2008
DOI: 10.1007/s11629-008-0170-4
|View full text |Cite
|
Sign up to set email alerts
|

A survey of fodder plants in mid-altitude Himalayan rangelands of Uttarakhand, India

Abstract: Himalayan rangelands, the crucial but by and large the neglected ecosystems, are an integral part of mountain farming systems. The present investigation is based on the extensive survey and collection of mid-altitude range plants from Almora and Champawat districts of Kumaun division in the Uttarakhand Himalaya in India, from September 2003 to June 2007. The rangelands studied were oak types, chirpine types, grass types and mixed ones. Some 300 species of grasses, other herbaceous plants, trees and shrubs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…The practice of farmers harvesting the fodder and transporting it as head loads to their houses and using the fodder in fresh or dry forms agrees with the findings of Gali et al (2006) from Argentina. Uses of fodder in fresh and dry conditions have also been reported by Singh et al (2008). Some plants like, Amranthus.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The practice of farmers harvesting the fodder and transporting it as head loads to their houses and using the fodder in fresh or dry forms agrees with the findings of Gali et al (2006) from Argentina. Uses of fodder in fresh and dry conditions have also been reported by Singh et al (2008). Some plants like, Amranthus.…”
Section: Discussionmentioning
confidence: 80%
“…A few studies have been conducted on fodder resources in the Uttarakhand Himalayas by Anonymous (1982), Jackson (1985), Bhatt and Rawat (1993), Singh (1985;1989;2002;2005), Jodha and Shrestha (1990), Singh and Bohra (2005), Singh and Gaur (2005), Bohra (2006), and Singh et al (2008). In the present paper, attempts have, therefore, been made to enlist plant species which are commonly used for cattle growing in the area.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that smallholder farmers in many parts of the world have a deep practical knowledge about the importance and quality of plants used to feed animals. Ethnobotanical investigations on fodder plants have been carried out in Africa [4][5][6], Brazil [7], India [8,9] and China [10][11][12]. Many studies throughout the world highlight the diverse and abundant use of grasses and sedges as fodder; grasses and sedges are generally reported to be palatable and highly productive resources and to have high forage potential especially in arid and semiarid areas [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is also used in ethnoveterinary medicine as an anthelmintic; a decoction of the leaves and buds of the plant are given to stock animals (e.g., horses, mules, sheep, and buffaloes) for round worm [ 320 ]. The plant is also used as a fodder plant in mid-altitude rangelands of Uttarakhand [ 321 ]. The essential oil from the aerial parts of A. parviflora collected from Pauri, Pauri Garhwal (Uttarakhand, India) was found to contain β-caryophyllene (15.3%), germacrene D (14.7%), camphor (11.4%), artemisia ketone (7.8%), and 1,8-cineole (5.8%) [ 61 ].…”
Section: The Genus Artemisiamentioning
confidence: 99%